ENHANCING ORAL PRESENTATION SKILLS THROUGH VIDEO PRESENTATION - Ahmad, Norazrina; Lidadun, Bernadette (PEOPLE: International Journal of Social Sciences, 2017)
Technology has evolved rapidly over the years and we cannot deny how significantly it has affected the teaching and learning process in the English language classrooms. Educators around the world use various technologies in their classrooms simply because they believe that technology could promote an interesting learning experience aside from being an effective learning tool. As such, the advent and abundance of newer technologies have allowed for the prevalent use of videos in the ESL classrooms because they can be used to stimulate ESL students in using the English language. With regard to this pedagogical development, this study looks at the impacts of video presentation production by ESL students, particularly in doing an assignment on a movie review. 111 undergraduate students were purposely selected as representative samples in the study. A set of questionnaire was devised and tested for reliability (Cronbach’s Alpha = 0.896) to collect data on the students’ experiences in their production of the video presentations. 12 video presentations were also selected and examined to describe how the students completed or approached their video presentation task. The findings demonstrate the potential of videos in motivating and enhancing students’ experiences and skills in ESL learning especially in terms of oral presentation skills as well as strategic planning and creativity. This was not only bound in a classroom setting but also beyond this boundary.